Creating balance? international perspectives on the work-life integration of professionals - Kaiser, Stephan; Ringlstetter, Max Josef; Eikhof, Doris Ruth; Pina e Cunha, Miguel (Springer eBooks., 2011)
A satisfactory and healthy integration of work with other life domains is one of the key challenges of modern society. Work-life balance and work-life integration have become focal points of today's human resource management practice and theory. Professionals who have been described as "extreme workers" regarding their work hours and engagement are under particular pressure to balance work and "the rest of life". This collection maps the increasingly extensive discussion of work-life issues for professionals and discusses key aspects in depth. What is work-life integration? What are the specific challenges for professionals? How do they manage their blurred work-life boundaries? How can companies intervene? Internationally leading authors discuss antecedents and individual and organizational outcomes of work-life integration, gender-specific perspectives and challenges as well as the use and usefulness of corporate work-life balance initiatives. In five sections distinguished researchers from across the world present experiences and research findings to provide a compendium of academic and applied research on the work-life integration of professionals. Cutting-edge research and novel theoretical perspectives make this collection a source of knowledge and inspiration for academic and business audiences interested in work-life integration issues in general and in the case of professionals in particular.